The future of the Australian valuation profession: New knowledge, emerging trends and practices. Issue 3 (18th June 2018) - Wilkinson, Sara; Antoniades, Hera; Halvitigala, Dulani
Abstract : Purpose: Valuers face significant challenges as processes become automated and the role evolves to data handling and processing. To survive and thrive, valuers must respond to a changing market. The purpose of this paper is to examine the issues, threats and challenges facing the Australian profession, though the issues are global. Design/methodology/approach: This qualitative research sought a deeper understanding of the threats, challenges and new areas of practice that Australian valuers were experiencing. A focus group approach was designed to collect data from practitioners in Sydney and Melbourne. The research aimed to identify new knowledge and skills for the future and emerging trends and practices. Findings: The key issues, threats and challenges faced included increasing use of automated valuation models for low-risk residential valuations, valuers being unable to protect themselves against the banks, loss of control of the data and valuations. In total, 12 knowledge domains and skills required in the future were established and ten emerging trends and practices were identified. Research limitations/implications: The key limitations were that participants were from Melbourne and Sydney in Australia only and the focus is NSW and Victoria centric, although many participants have international work experience. There was an under representation of rural valuers, of small valuation firms, of young, recently joined or qualified valuers and females. Practical implications: The findings inform a manifesto for the future which sets out the practical implications for valuers and the professional body. This action plan sets the new knowledge domains, practices and trends that can be adopted by the profession and its members. Originality/value: This is the original research and highlights some real threats, issues and challenges facing the Australian valuers. It complements work undertaken by legal and accounting professional bodies, which sense change affecting their membership and services. A manifesto for action has been outlined to address the changes that are coming and those already here.